Respon Masyarakat Kota Malang Terhadap Besaran Tarif Parkir Ditinjau dari Aspek Maqasid Syari`Ah - mohamad mafrukhi (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This research aims to discuss the response of Malang against quantities in terms of parking tariff aspects of Maqasid Shariah. This type of research is empirical legal research using the method of approach and a conceptual approach statue approach. Then data capture methods supported the primary data used is data acquired directly through the interview toward malang and secondary data obtained by examining references. Data analysis was done by way of editing and verifying data obtained from field melaluli interview. Then clasifying data obtained from the informant, further analysis of the data is already collected by Maqasid Shariah. Research results, obtained the first parking tariff quantity that is considered damning for most communities in the city of malang, however some people assume that the magnitude of the rate for parking is reasonable given the unfortunate town parking rates equal to other big cities like surabaya, both in terms of aspects of Maqasid Shariah then the quantity of parking rates, because it is considered more cause damage.